CO2 hydrogenation to formate by palladium nanoparticles supported on N-incorporated periodic mesoporous organosilica - Betsy, K. J.; Lazar, Anish; Pavithran, Anjuna; Vinod, C. P. (ACS Sustainable Chemistry & Engineering, 2020)
Development of a heterogeneous catalyst capable of selective transformation of CO2 to valuable products still remains a challenge. In this article, we account for the surfactant-directed synthesis of a new framework-incorporated nitrogen-containing periodic mesoporous organosilica nanosphere (NPMO). A thoroughly characterized N-incorporated hybrid PMO was utilized as a platform for stabilizing well-dispersed and easily accessible Pd nanoparticles (Pd-NPMO) without using any stabilizing agents or expensive dendrimers. Further, this bifunctional hybrid catalyst has been demonstrated to heterogeneously catalyze aqueous phase CO2 hydrogenation (CO2/H-2 ratio 1:3) for the direct synthesis of formate under 4 MPa pressure and at 100 degrees C. To validate the superior performance of the Pd-NPMO catalyst, we compared the activity with Pd-SBA-15 catalysts, and the results showed a 10-fold increase in turnover frequency of 108 h(-1) using Pd on NPMO which envisaged the crucial role of nitrogen sites in this catalyst to boost the CO2 valorization to formate.
Keywords: CO2 hydrogenation; Formic acid synthesis; Hybrid silica; Pd nanoparticles; PMO

Engineering pore morphology using silica template route over mesoporous cobalt oxide and its implications in atmospheric pressure carbon dioxide hydrogenation to olefins - Gupta, Sharad; Ciotonea, Carmen; Royer, Sebastien; Dacquin, Jean-Philippe; Vinod, C. P. (2020)
Highly ordered mesoporous cobalt oxides (denoted as m-Co-KIT-6 and m-Co-SBA-15) with three dimensional and two dimensional pore morphology respectively have been synthesized using 3D KIT-6, and 2D SBA-15 as silica template via nanocasting route. CO2 hydrogenation activity was evaluated for these mesoporous materials under atmospheric pressure conditions. In comparison to nanoparticles of cobalt oxide (Co3O4-nano), mesoporous catalysts showed excellent activity for CO2 hydrogenation due to their higher number of exposed active sites and lower mass diffusion limitations. The ordered mesoporous structure of Co3O4 catalysts favored the chain growth of carbon atoms for the production of C2+ hydrocarbons while Co3O4 nanoparticles showed strong selectivity toward CH4. High selectivity for C2+ (similar to 25%) was obtained for both m-Co-KIT-6 and m-Co-SBA-15 catalysts at 320 degrees C. In addition, the 3D pore structure of m-Co-KIT-6 catalyst exclusively formed more olefins (54.9%) fraction. (C) 2020 Published by Elsevier Ltd.
Keywords: CO2 hydrogenation; Mesoporous CO3O4; Olefin fraction; Pore morphology; Silica hard template

Role of metal-support interaction for atmospheric pressure CO2 hydrogenation over Pd/(Ti)-SBA-15 catalyst: effect of titanium composition on products selectivity - Soni, Yogita; Gupta, Sharad; Vinod, C. P. (Molecular Catalysis, 2021)
The potential role of metal-support interaction for tuning the product selectivity during atmospheric pressure CO2 hydrogenation has been demonstrated on Pd/(Ti)-SBA-15 catalyst. Highly dispersed Pd NPs on SBA-15 (Pd/ SBA-15) was synthesized and further modified with titanium of varying composition. Comparison of catalytic activity of Pd/Ti-SBA-15 with its counterparts (Pd/SBA-15 and Pd/TiO2) illustrated the significance of strong PdTi interface in this catalyst and its role in tuning the product selectivity of CO2 hydrogenation. The generation of an ample amount of oxygen vacancies in the Pd/Ti-SBA-15 catalyst with maximum metallic Pd sites in close vicinity of Ti is proposed to boost the CO2 hydrogenation activity.
Keywords: CO2 hydrogenation; Metal-support interaction; Modified deposition precipitation; oxygen vacancies; Titanosilicates

Exploring the electronic modulation in controlling the activity and selectivity of Ni-Au-In based catalyst in atmospheric pressure CO2 hydrogenation - Bajpai, Jyotsna P.; Gupta, Sharad; Goud, Devender; Deka, Diku Raj; V. Jagtap, Anuradha; Kumar, Pawan; Ahamed, Momin; Peter, Sebastian C.; Vinod, C. P. (Chemical Engineering Journal, 2025)
Nickel-based catalysts are widely used for the hydrogenation of CO2 but encounter stability challenges during prolonged reactions and at elevated temperatures. At atmospheric pressure, nickel primarily promotes methane formation in CO2 hydrogenation reactions. In this work, we demonstrate that the stability and activity of nickel can be significantly enhanced through gold (Au) modification. Furthermore, we achieve a near-complete selectivity switch from methane to CO by incorporating indium (In), mediated through the formation of Au-In alloy. This catalyst exhibits excellent CO2 conversion and CO selectivity at relatively lower temperatures (400 degrees C), addressing a major bottleneck in the Reverse Water-Gas Shifts (RWGS) reaction. XPS studies demonstrate an interesting electron transfer mechanism facilitated by gold, which involves the formation of electronrich Au species (Au delta-) and the development of Au-In alloys. This process improves the reducibility of nickel oxide while allowing a fraction of nickel to remain in its metallic form, managing a facile hydrogenation process and regulating the shift in selectivity from CH4 to CO.
Keywords: Alloy formation; Bimetallic catalyst; CO2 hydrogenation; RWGS; Selectivity switch; synergy; Trimetallic catalyst; XPS (X-ray photoelectron spectroscopy)